Investigation of Multiwavelength Performance Based on Different SOAs - Muridan, Norasmahan; Awang Lah, Airull Azizi; Md. Yusoff, Nelidya; Abdullah, Fairuz; Hamzah, Azura; Sulaiman, Abdul Hadi (International Journal of Integrated Engineering, 2021)
We investigated multiwavelength fiber laser (MWFL) performance using different types of semiconductor optical amplifiers (SOAs) utilizing Lyot filter as comb filter. The lasing performances of linear SOA (LSOA), nonlinear SOA (NLSOA) and booster optical amplifier (BOA) at different current settings were observed. Among the three SOAs, LSOA has the best lasing performance due to the lowest peak power difference with the highest number of lasing lines, a high ER value of 42 dB and considerable high peak power of -14.1 dBm at 550 mA. The multiwavelength laser is stable within 60 minutes at power fluctuation of less than 0.2 dB. The output spectra at 550 mA for all the SOAs are 70 nm to 80 nm wavelength difference from the ASE spectra.